2021
DOI: 10.4314/rjmhs.v4i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Skills on Triage among Nurses Working in Emergency Departments in Referral Hospitals in Rwanda

Abstract: BackgroundUnpredictable numbers of patients attending emergency departments highlight the need for Triage. Triage which is the prioritization of patient care based on severity of illness or injury, prognosis, and availability of resources is effective when clinicians are knowledgeable and skilled to perform it.ObjectiveTo assess knowledge and skills on triage among nurses working in emergency departments of Rwandan referral hospitals.MethodsCross-sectional analytical design was adopted. ninety-six (96) nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Kerie et al (2018) and Al-Rawee et al (2022) also reported moderate levels of clinical competence in triage nurses in terms of professional knowledge and clinical skill [ 6 , 24 ]. This is while the results of studies by Duko et al (2019), Twagirayezu et al (2021), Haghdoust et al (2011), and Haghigh et al (2017) showed that emergency nurses had inadequate/low levels of triage knowledge and skills [ 1 , 15 , 18 , 25 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Kerie et al (2018) and Al-Rawee et al (2022) also reported moderate levels of clinical competence in triage nurses in terms of professional knowledge and clinical skill [ 6 , 24 ]. This is while the results of studies by Duko et al (2019), Twagirayezu et al (2021), Haghdoust et al (2011), and Haghigh et al (2017) showed that emergency nurses had inadequate/low levels of triage knowledge and skills [ 1 , 15 , 18 , 25 ].…”
Section: Discussionmentioning
confidence: 93%
“…The triage knowledge of the nurses was also low in a study by Bista et al (2022) in Kathmandu, Nepal [ 17 ]. Moreover, the results of a study by Twagirayezu et al (2021) in Rwanda showed the inadequate level of triage knowledge and skills among nurses [ 18 ].…”
Section: Introductionmentioning
confidence: 99%